An Evaluation of Pain Induced by Intermaxillary Elastic Use - Zeynep Değirmenci; Faik Serhat Özsoy; Ömür Polat Özsoy (Turkish Journal of Orthodontics, 2010)

(untitled)
Aim:Intermaxillary elastics, which are frequently used in fixed orthodontic treatment, cause pain and discomfort and this affects patients' cooperation negatively. The aim of this study is to evaluate pain levels during intermaxillary elastic use for the first time.Subjects and Methods:Sixteen orthodontic patients (9 girls, 7 boys; mean age 16.21 ± 3.01) whom were to use intermaxillary elastics for the first time agreed to participate to the present study. A visual analog scale form was given to each patient to measure the subjective pain levels. After the collection of the forms, pain levels were measured on the forms by the same investigator using a digital caliper. Data evaluation was made with descriptive statistical analysis.Results:The pain level was started to increase two hours after the elastic application. The highest pain level was achieved at 6th hour and the same night. The pain level was started to decrease at the day 2 and at the day 7 only a few patients reported that they had still pain. The pain perception during biting was felt at the posterior teeth more than the anterior teeth.Conclusion:As a conclusion, the patients should be informed about the pain during intermaxillary elastic use and analgesic use for the first 3–4 days is strongly recommended to increase cooperation.